Psychological approaches to the study of saving - Ölander, Folke; Seipel, Carl-Magnus (Urbana : Bureau of Economic and Business Research, University of Illinois, 1970)
This report is an account of the results from the first stage of a research project which aims at elucidating certain aspects of individual saving with the aid of psychological and other behavioral science methods. It also examines the business cycle theories as it concerns individual savings.
Bibliography: p. 95-114.
usc 12/7/17
Loans
Keywords: Saving and investment